MONSOON ONSET OVER SELECTED EASTERN BOUNDARY CITIES OF PAKISTAN - Faisal, N.; Sadiq, N. (The Nucleus, 2012)
Vagaries of monsoonal rainfall are the main cause of flooding in Pakistan which washed away standing crops in rural areas and damage the infrastructure of the cities. This study is an attempt to estimate, analyse and depict the monsoon onset characteristics over the eastern boundaries of Pakistan on the basis of available diurnal rainfall data for the period 1961-2010. For this aim pentad monsoonal rainfall calculation (in which total amount of rain should not be less than 20mm) with the condition of at least three days of rainfall employed. Early and delayed dates are also calculated for the said period of eight stations viz Lahore, Islamabad, Khanpur, Bahawalnagar, Rohri, Chhor, Sialkot and Bahawalpur. After standardizing the data, distance method is used to plot the contours. The results reveal mean dates of monsoon onset, ranges from the end of June (27th June) to start of August (1st August). As regards, delayed and earliest starting monsoon dates, it lying from 3rd of August to 17th of September and from 30th May to 25th of June respectively. It appears that delayed onset dates are rather scattered than the earliest ones. Findings of this paper may be helpful to the farmers, planners and forecasters of this discipline.